2009
DOI: 10.1007/s00299-009-0796-x
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional differences in gene families of the ascorbate–glutathione cycle in wheat during mild water deficit

Abstract: When comparing the responses of two wheat (Triticum aestivum L.) genotypes, the drought-tolerant Plainsman V and the drought-sensitive Cappelle Desprez, to reduced amounts of irrigation water, we found differences in ascorbate metabolism: both ascorbate oxidation and transcription levels of enzymes processing ascorbate were changed. Relative transcript levels of ascorbate peroxidase (APX), monodehydroascorbate reductase (MDAR), dehydroascorbate reductase (DHAR) and glutathione reductase (GR) isoenzymes, predic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
1
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(47 citation statements)
references
References 59 publications
2
43
1
1
Order By: Relevance
“…Furthermore, lack of cAPX induction could be due to the fact that APX isoforms are present in multiple subcellular locations and belong to multigene families and protection from ROS could therefore be the result of induction of other isoforms. 55 Secenji et al 56 demonstrated that expression levels of two cytosolic and a thylakoidbound APX variants increased significantly in a drought-tolerant wheat cultivar while a cytosolic and a stromal APX coding transcripts were found to be higher in a drought-sensitive cultivar after a 4 week-long water deficit stress. Relevant findings by Sofo et al 57 suggest that ROS and their regulated metabolism might depend on species, cultivars/varieties, tissues, stress intensity and duration and antioxidant enzyme variants, further supported by the observed suppression of CAT in Medicago roots 9 and 11 d after water stress imposition which implies that CAT may be less important than cAPX in scavenging of H 2 O 2 in roots in long term stress.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, lack of cAPX induction could be due to the fact that APX isoforms are present in multiple subcellular locations and belong to multigene families and protection from ROS could therefore be the result of induction of other isoforms. 55 Secenji et al 56 demonstrated that expression levels of two cytosolic and a thylakoidbound APX variants increased significantly in a drought-tolerant wheat cultivar while a cytosolic and a stromal APX coding transcripts were found to be higher in a drought-sensitive cultivar after a 4 week-long water deficit stress. Relevant findings by Sofo et al 57 suggest that ROS and their regulated metabolism might depend on species, cultivars/varieties, tissues, stress intensity and duration and antioxidant enzyme variants, further supported by the observed suppression of CAT in Medicago roots 9 and 11 d after water stress imposition which implies that CAT may be less important than cAPX in scavenging of H 2 O 2 in roots in long term stress.…”
Section: Discussionmentioning
confidence: 99%
“…Latest findings by Sečenji et al (2010) who compared the responses of two wheat genotypes with differing capacity to withstand reduced water supply revealed major differences in ascorbate metabolism: both ascorbate oxidation and transcription levels of enzymes processing ascorbate were changed. Relative transcript levels of APX, monodehydroascorbate reductase (MDHAR), DHAR and GR isoenzymes showed different transcriptional changes in the two genotypes.…”
Section: Drought Stressmentioning
confidence: 98%
“…This elevation in GSH concentration is of vital importance, because it induces the signal transduction and defence against ROS which is achieved through a pathway with various control points, which include orchestrated activation of genes encoding enzymes related with glutathione metabolism (Sečenji et al 2010). Therefore, high levels of glutathione provide the cell with the ability to counteract the negative effects of oxidative stress syndrome (Srivalli and Khanna-Chopra 2008).…”
Section: Introductionmentioning
confidence: 98%
“…Four selected winter wheat cultivars were investigated with presumed contrasting behavior under water limiting conditions Sečenji et al, 2010;Fábián et al, 2011). In addition to two Hungarian cultivars (Mv Emese -tolerant, GK Élet -sensitive), the selection contained two well-known standard genotypes (Plainsman V -tolerant, Cappelle Desprez -sensitive).…”
Section: Discussionmentioning
confidence: 99%